Respuesta :
Step-by-step explanation:
Given
y + 1 = 3( x - 4)
y + 1 = 3x - 12
3x - y = 12 +1
3x - y = 13
Dividing both sides by 13 we get
3x - y = 1
13. 13
or x - y
13 13
3
Comparing with x/ a + y/b = 1
so
x-intercept(a) = 13/3
y-intercept (b) = 13
Answer:
X-intercept: (13/3, 0)
y-intercept: (0, -13)
Step-by-step explanation:
The x-intercept of a graph is the point of intersection between the x-axis and the graph. Since the x-axis is also the line y=0, the y-value of this point will always be 0.
The y-intercept of a graph is the point of intersection between the y-axis and the graph. Since the y-axis is also the line x=0, the x-value of this point will always be 0.
Finding x-intercept
0+1 = 3x -12
13=3x
x= 13/3
Finding y-intercept
y+1= -12
y= -13